PEMBERDAYAAN SATUAN KEWILAYAHAN DALAM MENGANTISIPASI RADIKALISME DAN SEPARATISME DALAM RANGKA MENJAGA KEAMANAN NASIONAL INDONESIA: (Studi Kasus Kodam Iskandar Muda / IM) - Agung Ika Jaya; Lukman Munawar Fauzi; Mochamad Nanang Nazmudin (Public Knowledge, 2026)
Indonesia has been a place of conflict due to its multicultural structure and diversity of ethnicities,religions, customs and more. Indonesia has had to face major problems, such as intra-state conflicts.The threat of state disintegration began to appear as a result of these conflicts. One form of conflict thathas occurred is the Aceh conflict. To anticipate social conflicts using a local wisdom approach, soldiersof the Iskandar Muda Military Region Command (Kodam IM), a regional unit under the command of theArmy Headquarters, are required to understand the culture and customs of the Acehnese people. They are also required to prevent the spread of separatism, which could threaten national security. In this research, the author will use Role Theory, because this theory is considered relevant to examine the issues raised. In addition, researchers will also use the concepts of Radicalism, Separatism, and National Security. The research method used by researchers is a qualitative approach and analytical descriptive research type. This research aims to know examine and understand the social processes centered on and efforts of Kodam IM in anticipating radicalism and separatism in Aceh in order to maintain Indonesia's national security.